Electrically control amplified spontaneous emission in colloidal quantum dots - Yu, Junhong (2020)
Colloidal quantum dots (CQDs) are highly promising materials for light amplification thanks to their efficient photoluminescence, tunable emission wavelength and low-cost synthesis. Unfortunately, CQDs are suffering from band-edge state degeneracy which demands multiple excitons to achieve population inversion. As a result, non-radiative Auger recombination increases the lasing threshold and limits the gain lifetime. Here, benefiting from the negative charging, we demonstrate that the amplified spontaneous emission (ASE) threshold is controllable in a device where CQD film is exposed to an external electric field. Specifically, singly charged CQDs lower the threshold due to the preexisting electron in the conduction band, while strongly enhanced Auger recombination in doubly charged CQDs stymies the ASE. Experimental results and kinetic equation model show that ASE threshold reduces 10% even if our device only charges ~17% of the CQD population. Our results open new possibilities for controlling exciton recombination dynamics and achieving electrically pumped CQD lasers.